Analisis Penentuan Harga Pokok Produksi menggunakan Metode Full Costing pada Kedai Rai Raka di Kabupaten Karawang tahun 2022 - Dinar Gustianing Tias; Sihabudin Sihabudin; Robby Fauji (IPM2KPE, 2024)
The aim of this research is to determine the calculation of the cost of goods produced at rai raka shop MSMEs using the full costing method. The type of data used is quantitative descriptive, namely in the form of production cost analysis and data, the data source is primary data from interviews conducted with company owners and observations, as well as secondary data sourced from literature studies and other literature that supports the writing of this research. The results of this research show that there are differences in the calculations according to MSMEs for Rai Raka shops using the full costing method. Calculations using full costing produce a greater value, this is because the calculation according to MSMEs does not take into account all components of factory overhead costs. Keywords: Cost of Goods Production, Full Costing Method, MSMEs